Management Model of Telemedicine Services in Post- Covid-19 Era: A Systems Thinking Approach - Megawati, Suci; Ansar, Muhammad Chaeroel; Lestari, Yuni (STI Policy and Management Journal, 2025)
To benefit community welfare, a set of policies to improve access to—and the quality of—basic health services by encouraging thorough efforts via technological adoption is necessary, such as by implementing telemedicine. This study aims to determine the readiness of telemedicine adoption and evaluate telemedicine implementation policies to enhance community welfare in the post-COVID-19 era. Using a case-study and qualitative descriptive method, the data were analyzed using Powersim Studio 10 through systems thinking approach. A post-COVID-19 Telemedicine Service Policy and Management Model was developed using system dynamics through simulation. Secondary data included COVID-19 case numbers and telemedicine platform usage during the pandemic. The findings reveal three key reinforcing loop (R) relationships in telemedicine service management: (1) the enhancement of service speed positively influences users’ convenience; (2) the improvement of telemedicine provision enhances the service simplicity and users’ convenience; and (3) a rise in telemedicine users stimulates improvements in service quality. These loops demonstrate mutual benefits, where advancements in one aspect positively affect others. These findings provide valuable insights for policymakers and providers to optimize telemedicine delivery in the post-pandemic era. Recommended actions include increasing public awareness of telemedicine's benefits and ensuring user-friendly platforms without compromising service effectiveness and efficiency.